Dialektologi Bahasa Arab: Analisis Perbedaan Linguistik Berdasarkan Kajian Pustaka - Ainur Rofiq Sofa; Ayun Febrianti (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2025)
This study discusses Arabic dialectology by highlighting the linguistic differences that emerge across various Arabic dialects. The analysis focuses on phonological, morphological, syntactic, and lexical aspects. The research method used is a literature review, drawing on academic sources such as journals, books, and previous studies related to Arabic dialectology. The data were analyzed using a descriptive-qualitative approach to identify forms of dialectal variation and the influencing factors, including geographical, historical, and sociocultural conditions. The findings indicate that the diversity of Arabic dialects reflects the linguistic richness and dynamic nature of Arabic-speaking communities. This study is expected to contribute to the body of knowledge in Arabic linguistics, particularly in the field of dialectology.